Corporate Governance, Incentives, and Industry Consolidations - Brown, Keith C.; Dittmar, Amy; Servaes, Henri (Review of Financial Studies, 2005)
Conference at the University of Michigan, and the AFA meetings for helpful comments and suggestions. We would especially like to acknowledge the insights and contributions that Ken Wiles (AppForge, Inc.) has provided to the paper. Anna Danielova and Andras Marosi provided excellent research assistance. Corporate Governance, Incentives, and Industry Consolidations Several changes, such as the advances in information technology and the advent of outsourcing, led to increases in optimal firm size in many fragmented industries over the last decade. This paper studies the determinants of the success of these industry consolidations using a unique sample of firms that were created at the time of their initial public offering: rollup-up IPOs. In these transactions, many small firms merge into a shell company, which goes public at the same time. This sample allows us to follow firms from the day they were established. We find that these firms deliver poor absolute and relative stock returns, on average. Their operating performance mimics that of other firms of the industry, but does not justify to their high initial valuations. However, the average performance hides substantial cross-sectional differences. If